(untitled) (Al-Academy, 2025)
The first decade of the current century witnessed a tangible acceleration in technological development in all fields, especially in the field of digital technologies in advertising design. This development has resulted in diversity and multiplicity in digital technologies, in terms of programs and materials used, and this research comes explaining those technologies, their aspects and what they are, and explaining the importance of choosing the appropriate type of technologies according to the tasks, capabilities, and temporal and spatial conditions, and explaining the importance of the graphic designer’s familiarity with that diversity. Within the limits of the capabilities and tools of design programs, and an explanation of the most important effective programs in designing indicative advertisements; Especially in the production of good pictures and indicative graphics, the research has produced many results regarding digital technologies, which lead to achieving a high degree of benefit, whether for the graphic designer, or for institutions related to indicative advertisements